Pengembangan Sistem Keamanan Data Berbasis Blockchain untuk Perlindungan Informasi Sensitif di Sektor Keuangan - Angga Rahmat Pinanggih; Nina Mardiana; Febryawan Yuda Pratama; Yessica Fara Desvia; Arman Maulana (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The protection of sensitive information in the financial sector requires a security architecture capable of preserving confidentiality, integrity, availability, auditability, and regulatory accountability across multiple institutions. Conventional centralized security models remain vulnerable to single points of failure, unauthorized access, data manipulation, and limited transparency in inter-organizational data sharing. Blockchain offers tamper-resistant records, decentralized trust, and verifiable audit trails; however, its direct implementation in financial systems is constrained by scalability limitations, smart contract vulnerabilities, privacy leakage, and conflicts between immutable ledgers and data protection principles. This study aims to develop a blockchain-based data security system for protecting sensitive financial information by integrating permissioned blockchain and Zero-Knowledge Proofs. The proposed method adopts a consortium-oriented permissioned blockchain architecture, represented by Hyperledger Fabric, to ensure controlled participation, certificate-based identity management, endorsement policies, and auditable transaction validation. Smart contracts are designed as policy-enforcement components for consent management, access authorization, data commitment, revocation, and audit logging. Zero-Knowledge Proofs are incorporated to verify customer attributes, eligibility, and access rights without disclosing raw personal or financial data. Sensitive information is stored off-chain in encrypted form, while the blockchain records only cryptographic commitments, hashes, consent states, and audit events. The expected result is a security model that improves data integrity, controlled access, privacy-preserving verification, and compliance-oriented accountability while reducing unnecessary exposure of sensitive data on-chain. The implication of this research is the provision of a technically coherent framework for financial institutions seeking to adopt blockchain securely in regulated environments, especially where data confidentiality, auditability, and privacy compliance must be achieved simultaneously.